Study Socio-Economic Condition of Women Prisoners: Understanding the Challenges Faced by Women Prisoners in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Despite the fact that exploration is consistent in underlining the especially adverse impacts of jail on women, their extraordinary necessities are infrequently mulled over. The adjustment in the creation of the jail populace has featured the deficiencies in practically all jail frameworks in gathering the gender-explicit necessities of women detainees. Any cutting edge way to deal with give a more worthy criminal equity strategy for women should focus better on their issues. Specifically there is need to concentrate on the circumstance of women and children in the jail and apply gender viewpoint to arrangements and program for them. In India, a couple of studies worth their name have been directed on jail life of women criminals.